TINDAK ILOKUSI DIREKTIF DALAM DRAMA SERI HOTARU NO HIKARI 2 EPISODE 1-5 KARYA MIZUHASI FUMIE - WIDASARI, INTAN (Jurnal Ilmiah Mahasiswa FIB, 2013)
Humans as social beings require language as a communication tool. Communication is the product or result of a symbol, word or phrase in the form of speech act behavior. Speech act consists of 3 types. They are locutions, illocutionary and perlocution. Illocutionary acts are doing an act in saying something. Among directive illocutionary acts that function to produce an effect in the form of the action taken by the hearer. Japanese directive illocutionary acts can be seen in everyday conversation as a conversation in drama such as Hotaru no Hikari 2. The method used in this research is descriptive qualitative. This study uses the theory of Searle reference for classifying the type of directive illocutionary acts such as orders, requests, demands, restrictions, and recommendation, suggestion or advice, and Leech theory to analyst views illocutionary function of the level of politeness. The research found 5 types of directive illocutionary acts such as orders, requests, demands, restrictions, and recommendation, advice or counsel. Later found to be 4 types of illocutionary function of the level of courtesy that is competitive, convivial, collaboration, and conflictive.   Key words: illocutionary acts, directive illocutionary.